2021
DOI: 10.1021/acsomega.1c00727
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Growth of Uniform Monolayer MoS2 Nanosheets by Metal–Organic Chemical Vapor Deposition

Abstract: To achieve large area growth of transition metal dichalcogenides of uniform monolayer thickness, we demonstrate metal–organic chemical vapor deposition (MOCVD) growth under low pressure followed by a high-temperature sulfurization process under atmospheric pressure (AP). Following sulfurization, the MOCVD-grown continuous MoS 2 film transforms into compact triangular crystals of uniform monolayer thickness as confirmed from the sharp distinct photoluminescence peak at 1.8 eV. Raman and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 51 publications
5
21
0
Order By: Relevance
“…Additional data on the optical characterization of the MoS 2 grown using the conventional CVD method are shown in Supplementary Materials Figure S1 . The growth of such thick MoS 2 films and partial formation of monolayer MoS 2 have been commonly observed in MoS 2 growth by the conventional CVD method using MoO 3 and S powder as precursors [ 30 , 31 , 32 , 33 , 34 ]. An AFM height image of monolayer MoS 2 shows small particles grown nonuniformly on the surface of monolayer MoS 2 ( Figure 1 g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional data on the optical characterization of the MoS 2 grown using the conventional CVD method are shown in Supplementary Materials Figure S1 . The growth of such thick MoS 2 films and partial formation of monolayer MoS 2 have been commonly observed in MoS 2 growth by the conventional CVD method using MoO 3 and S powder as precursors [ 30 , 31 , 32 , 33 , 34 ]. An AFM height image of monolayer MoS 2 shows small particles grown nonuniformly on the surface of monolayer MoS 2 ( Figure 1 g).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the chemical vapor deposition (CVD) method can control the number of MoS 2 layers and enables wafer-scale synthesis [ 27 , 28 , 29 ]. However, the conventional CVD method using MoO 3 and S powder has a problem in that thick MoS 2 films are formed in the center of the substrate and only MoS 2 monolayers are generated at the edge of the thick MoS 2 films [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 321,375,376 ] Researchers observed that the addition of selected synergistic additives, such as a small amount of O 2 , N 2 , or H 2 O vapor, [ 185,377 ] or the seed promoter (e.g., aromatic molecules), [ 378–380 ] to the CVD process, can result in large‐area, uniform, crystalline monolayer materials with exceptional optical and electrical properties. [ 198,381,382 ] For example, Asif et al [ 377 ] used water‐assisted CVD for synthesizing multilayer graphene. With increased water vapor concentration from 0 to 2000 ppmv, graphene layers increase from 2 to 25 layers.…”
Section: The Preparation Of 2d Materialsmentioning
confidence: 99%
“…However, this method of referencing that corresponds to adventitious carbon contaminations might be erroneous as the elemental composition and thickness of the film vary. 60 The chemical composition of the grown film was quantified using the Casa XPS software. In the deconvolution process, some of the peak parameters like binding energy, FWHM, peak area, etc., were kept fixed 61 and the fitting of the spectra were performed using either a combination of the Gaussian/Lorentzian function with GL line shapes (with varying FWHM for component peaks) or with the Voigt function following a Shirley background correction.…”
Section: Experimental Techniquesmentioning
confidence: 99%